Teuer Furniture. (B), Multiples valuation - Petersen, Mitchell A. ([London] : SAGE, 2016)
Teuer Furniture is a privately owned, moderately sized chain of upscale home furnishing showrooms in the United States. By the end of 2012, it had regained its financial footing and a number of long-term investors, including several of Teuer's original non-management investors, now want to sell their shares. At the request of the board, Jennifer Jerabek, the chief financial officer of the company, put together a valuation of Teuer based on a discounted cash flow analysis. When the figures were put to investors, a number of them disagreed with the results. This study examines how Teuer addressed these differences.
Originally Published in: Petersen, M. A. (2014). Teuer Furniture (B): Multiples Valuation (teaching notes revised 10/07/2015). 5-313-509(B). Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Business enterprises -- Finance -- Case studies